Dimensions of Spiritual Education in The Tradition of Grave Pilgrimage in Javanese Muslim Society - Damanhuri; Roibin; Jamilah (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to identify and analyze the dimensions of spiritual education in the tradition of grave pilgrimage among the Javanese Muslim community. The approach employed in this study is a systematic literature review, which enables the researcher to compile findings comprehensively based on published scholarly sources. Data were collected from a range of academic literature, including journal articles, scholarly books, and relevant documents discussing aspects of spirituality, Javanese culture, and Islamic education. The analysis was conducted using a descriptive-qualitative method, emphasizing the interpretation of concepts and spiritual educational values embedded in the practice of grave visitation. The findings of this study indicate that the tradition of grave pilgrimage contains important spiritual educational elements for the formation of religious consciousness, the appreciation of life values, and emotional closeness to ancestors. Findings from the perspective of Javanese Muslim pilgrims indicate that grave pilgrimage is viewed as a form of worship, seeking blessings, and religious tourism. This practice also has implications for the development of religious and cultural identity. It can be used as an educational experience that combines spiritual, artistic, and educational elements in Islamic education. This study contributes to a deeper understanding of the values and practices contained in the tradition of grave pilgrimage, as well as its relevance in the context of spiritual-based education and the development of religious and cultural identity in Java.